TINGKAT BELAJAR MANDIRI DI MASA PANDEMI COVID – 19 DALAM HUBUNGANNYA DENGAN HASIL BELAJAR SISWA - Yesi Meliani; Budiman Tampubolon; Suparjan Suparjan (Universitas Tanjungpura, 2022)
This study aims to describe the level of student independent learning during the Covid-19 pandemic in thematic learning in relation to the learning outcomes of fourth grade students at 39 public elementary schools, Pontianak City. The method used The method used is a descriptive method in the form of relationship studies (interrelationship studies) using a correlation study research method (correlation studies). The population in this study found 33 students. Data collection techniques in this study were interviews, questionnaires (questionnaire), and document collection. The data collection tools used are questionnaires and student daily test scores. The results of the study showed that student self-study during the COVID-19 pandemic, grade IV at 39 Pontianak City Elementary School, which was 84.06% was classified as a good result. Meanwhile, the learning outcomes of fourth grade students at 39 Pontianak City Elementary Schools are in the form of average daily test scores for Theme 1 and Theme 2 students in the odd semester for the 2021/2022 academic year, which consists of 33 students, which is 61.75%, which is included in the sufficient category. The results based on calculations using the product moment correlation formula for student self-study calculations with test scores obtained rcount of 0.470, while the rtable of 0.355 means rcount > rtable or (0.470 > 0.355). Based on the research, the relationship between independent learning during the COVID-19 pandemic and the learning outcomes of fourth grade students at 39 Pontianak City Elementary School is included in the category.